PENGARUH PENGGUNAAN MEDIA AJAR NUMBER LINE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DALAM OPERASI BILANGAN BULAT PADA SISWA KELAS IV DI MIS CIOMAS - Lastri Kurniasih; Repi Heryanto; Yaya Yulia Bonita; Rindy Mulyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low mathematical problem-solving skills of fourth-grade students regarding integer operations at MIS Ciomas. This was indicated by pretest results that remained below the Minimum Passing Criteria (KKM), suggesting that students struggled to understand the abstract concept of integers. The lack of concrete learning media is one of the factors contributing to students’ low understanding. The purpose of this study is to determine the effect of using the Number Line teaching media on mathematical problem-solving skills in integer operations among fourth-grade students at MIS Ciomas. The research method used is a quantitative method with a one-group pretest-posttest pre-experimental design. The research sample consisted of 25 students. Data collection was conducted through tests (pretest and posttest), which were then analyzed using normality tests, homogeneity tests, hypothesis tests, and N-Gain tests to determine improvements in learning outcomes. The results of the study indicate that there was a significant improvement in students’ mathematical problem-solving skills after using the Number Line teaching medium. The average pretest score of 51.60 increased to 83.40 on the posttest, representing an increase of 31.80 points. Additionally, the NGain test results showed an average value of 0.6746, or 67.46%, which falls into the moderate-to-high category, indicating that the Number Line teaching aid is effective in improving students’ abilities. The conclusion of this study is that the use of the Number Line teaching medium has a significant and effective impact on improving students’ mathematical problem-solving skills in integer operations. This medium helps students understand abstract concepts more concretely, thereby improving learning outcomes.